Prediction of elastic properties of precipitation-hardened aluminum cast alloys - Suh, Jin-Yoo; Lee, Young-Su; Shim, Jae-Hyeok; Park, Hoon Mo (ELSEVIER SCIENCE BV, 2012)
A methodology is proposed for predicting the elastic properties of precipitation-hardened alloys by combining different modeling techniques: the CALPHAD method, first-principles calculation, and elasticity models. The proposed procedure was applied to conventional aluminum cast alloys to predict their elastic moduli. The predicted Young's moduli are in reasonable agreement with values reported in the literature, which verifies the potential applicability of the methodology to the development of high-stiffness aluminum cast alloys. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: THERMAL-EXPANSION; ELECTRON-GAS; CONSTANTS; SILICON; APPROXIMATION; MODULI; 1ST-PRINCIPLES; TEMPERATURE; INCLUSIONS; PRESSURE